The bionomics and control of the silver mite Hemitarsonemus latus (Banks)(Acarina : Tarsonemidae) on lemons - Schwartz, A.(Allen) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1965.